Analysis of the Role of Internal Control of the Sales and Collection Cycle in Improving Sales Effectiveness in a Case Study of PT Mayora Indah Tbk for the Period 2022–2024 - Meutia Zahra Ramadhani; Nur Anisa; Fatur Rahmi; Brigitta Clecia Paredanun; Ariel Syam; Samirah Dunakhir; Alia Rezki Amalia (Journal of Innovative and Creativity, 2025)
This study investigates the role of internal control in the sales and collection cycle to enhance sales effectiveness at PT Mayora Indah Tbk during 2022–2024. The research aims to analyze how internal control mechanisms impact sales performance and cash flow quality. Employing a descriptive quantitative approach with a longitudinal case study design, the population consists of all financial and operational data related to sales and collections. Purposive sampling was used to select annual financial reports, accounts receivable records, inventories, and supporting documents. Data were analyzed using financial ratio analysis and COSO-based internal control evaluation. The findings reveal that the implementation of credit authorization, integrated order processing, separation of collection and cash receipt duties, and technology-based receipt monitoring led to increased sales, improved collection quality, and a higher cash realization ratio. However, challenges remain in inventory management, as indicated by rising days inventory outstanding and cash conversion cycle. The study concludes that comprehensive internal control strengthens operational efficiency and cash flow stability.